INTERNATIONAL EXPERIENCES OF MANAGEMENT OF ENTERPRISES ON THE BASIS OF BUDGETING (Marketing Journal, 2025)
This article studies international experience in managing enterprises based on budgeting. In particular, the theoretical and practical aspects of adaptive and complex budgeting systems are covered through the analysis of the scientific works. The article analyzes advanced international models such as “Beyond Budgeting”, “Zero -Based 526 Budgeting”, “Rolling Forecasts”, “Balanced Scorecard” and “EVA (Economic Value Added)”, and justifies their role in increasing flexibility, transparency and efficiency at the strategic and operational levels in enterprise management. At the same time, the possibilities of gradually integrating these models into the national management system in the practice of Uzbek enterprises are analyzed. The results of the study indicate the need to introduce innovative approaches in the national management system.
Keywords: budgeting; international experience; adaptive budgeting; zero -based budgeting; strategic management; financial planning; management efficiency; KPI system